Green Logistics Development of Express Companies in the Context of “Dual Carbon” Strategy Research - Hu, Die; Cao, Zhengyan (International Journal of Global Economics and Management, 2024)
In the context of "dual carbon", green logistics as an emerging concept type, not only plays an important role in environmental protection and sustainable economic development, but also can bring great economic benefits to express delivery companies. However, the current development of green logistics technology in China is not mature enough, resulting in the transformation of the courier company is facing the situation of opportunities and challenges. In this paper, we sort out the "dual carbon" background of the development of green logistics courier company status quo, analyze the courier company in the process of transition to green logistics problems and targeted to put forward the corresponding measures to solve them, and hope to be able to other courier company’s green logistics development to provide reference and reference.